Assessment of Tissue Perfusion Following Conventional Liposuction of Perforator-Based Abdominal Flaps - Akdeniz Doğan, Zeynep Deniz; Saçak, Bülent; Yalçın, Doğuş; Pilancı, Özgür; Tuncer, Fatma Betül; Çelebiler, Özhan (Archives of Plastic Surgery, 2017)
Background The effect of liposuction on the perforators of the lower abdominal wall has been investigated in several studies. There are controversial results in the literature that have primarily demonstrated the number and patency of the perforators. The aim of this study was to determine the effect of liposuction on the perfusion of perforator-based abdominal flaps using a combined laser–Doppler spectrophotometer (O2C, Oxygen to See, LEA Medizintechnik).Methods Nine female patients undergoing classical abdominoplasty were included in the study. Perforators and the perfusion zones of the deep inferior epigastric artery flap were marked on the patient's abdominal wall. Flap perfusion was quantitatively assessed by measuring blood flow, velocity, capillary oxygen saturation, and relative amount of hemoglobin for each zone preoperatively, after tumescent solution infiltration, following elevation of the flap on a single perforator, and after deep and superficial liposuction, respectively.Results The measurements taken after elevation of the flap were not significantly different than measurements taken after the liposuction procedures.Conclusions The liposuction procedure does not significantly alter the perfusion of perforator-based abdominal flaps in the early period. The abdominal tissue discarded in a classic abdominoplasty operation can be raised as a perforator flap and has been demonstrated to be a unique model for clinical research.
Keywords: Perforator flap; Spectrophotometry; Lipectomy